The Blue Growth Challenge to Maritime Governance - Guerreiro, José (Frontiers in Marine Science, 2021)
In 2006 the European Union (EU) began a dramatic change in its conception and approach to maritime policy. By developing what was called Integrated Maritime Policy, there was an attempt to coordinate different sectorial policies and thus adding value, through synergies and economies of scale. At the same time, and as a result of scientific and technological advances, five strategic sectors with great growth potential were identified: aquaculture, renewable energies, blue biotechnology, deep sea mining, and nautical tourism. These were the pillars for the Blue Growth Strategy, leading to more jobs and global economic growth. This trend quickly spread to other continents, universalising the concept of blue growth. However, the growing competition for maritime space, due to new uses, led to the realisation that along with the need to ensure confidence and stability for investors, it would be imperative to develop new planning and management instruments for these spaces. During this process, governments quickly realised that this evolution, which had the potential for far reaching economic and social impacts, required a new institutional framework adapted to this new reality, which would end up having an impact on the governments structure itself. We have witnessed, particularly during the last decade, a profound conceptual change in the governance of maritime space. The design of new political, legal, institutional, and governmental frameworks, which are introducing a new model of maritime and marine governance at a global scale, are probably the most critical one since World War II. This article develops this analysis, based on several examples, both in the EU as well as in other countries outside the bloc, particularly those surrounding the Atlantic, in order to demonstrate that the drive towards a blue economy triggered a profound and deep change in marine policies and governance.